Effects of simulated diesel contamination on soil fauna community - XIAO Jiujin; YANG Litong; YANG Zhifu; FENG Qiuhong; CHEN Lianghua; HU Zongda (浙江大学学报. 农业与生命科学版)
Soil fauna is an important component of soil ecosystem, which plays a significant role in the decomposition of biological remains, soil properties and the enhancement of material recycling and energy conversion in soils. This study aimed to find the changes of soil fauna community with different diesel concentration levels, and to investigate the response of soil fauna community to diesel contamination. Five different diesel contamination levels were conducted in the filed which was located in Chengdu, Sichuan Province. Soil macro-fauna were picked up by hand and investigated by dry-wet funnel method. A total of 21 135 individuals of soil fauna, belonging to three phyla, nine classes, 20 orders and 54 groups, were collected. Nematoda and Araneae were the dominant groups, which counting for 54.88% and 14.82%, respectively, of the total. The highest percentage of nematoda was found in the treatment with 240 g/m2 diesel in July, which counted for 70.94%, and the lowest was found in the control treatment (CK, 0 g/m2 diesel) in August, which counted for 36.15%. Compared with the CK, diesel contamination decreased Shannon-Wiener index, Pielou index and Margalef index, which showed a trend of first increasing and then decreasing with the diesel contamination level increasing in the same month. The monthly dynamic variation ranges of density and group number of soil fauna increased because of diesel contamination, and the soil fauna density decreased with the diesel contamination level increasing in each month. The vertical distribution rule of soil fauna was changed by diesel contamination, and the characteristics of gathering on soil surface were destroyed, even the inverse distribution was found in some plots. Meanwhile, the soil fauna community recovered with the time passing by. Compared with soil fauna groups, soil fauna density was easier affected by the diesel contamination levels.